مقاومة القبائل الليبية في منطقة سرتيس للوجود الإغريقي والروماني مابين القرن الخامس ق م وإلى نهاية القرن الأول الميلادي - سالم عمر العقيلي فاطمة (مجلة كلية الاداب, 2024)
The Libyan resistance of the Libyan tribes in the Sirtes area to the Greek and Roman presence through literary sources and archaeological remains.. The topic of this research deals with the national resistance movement of the Libyan tribes in the Sirtes area to the Greek and Roman presence through literary sources and archaeological remains. The great powers were the Greeks, the Carthaginians, and then the Romans. The aspirations of these forces to extend their influence and control this region caused these tribes to engage in this conflict to prove their right to their homeland at times and to repel aggression and domination at other times. This conflict reached its climax in the Roman era, when it developed into an armed clash in which Roman consuls were pushed against these tribes to subjugate them and perhaps also to try to change the tribal ethnicity in the region.